Adaptive uniform polar quantization - Perić, Z.H.; Milojković, M.; Antić, D.; Jovanović, A.Z. (Реєстрація, зберігання і обробка даних, 2005)
A simple and complete analysis for an optimal uniform polar quantizer with respect to mean-square error (MSE) as efficient quantization technique for any number of points N (Fixed-Rate) is given. Conditions for the optimality of the polar quantizer and all main equations for phase partitions and optimal number of levels are presented. Improved performance over product polar quantization and scalar uniform quantization proposed in the literature is afforded by allowing a variable number of phases at each magnitude level.